Aspergillus Tracheobronchitis and Influenza A Co-infection in a Patient with AIDS and Neutropenia - Lee, Ji-Yong; Joo, Eun-Jeong; Yeom, Joon-Sup; Song, Jae-Uk; Yim, Seo-Hyung; Shin, Dong-Suk; Yu, Jung-Hee; Ju, Deok-Yun; Yim, Jae-Wan; Song, Young-Seok; Sohn, Yoon-Jeong; Do, Sung-Im (Infection & chemotherapy, 2014)
Aspergillus tracheobronchitis (AT), an unusual form of invasive pulmonary aspergillosis (IPA), is characterized by pseudomembrane formation, ulcer or obstruction that is predominantly confined to tracheobronchial tree. Hematologic malignancies, neutropenia, solid organ transplantation, chronic corticosteroid therapy and acquired immunodeficiency syndrome (AIDS) are known to be major predisposing conditions. However, since the introduction of highly active antiretroviral therapy, there is only one reported case of AT in AIDS patient. After pandemic of influenza A/H1N1 2009, there are several reports of IPA in patient with influenza and most of them received corticosteroid or immunosuppressive therapy before the development of IPA. We present a 45 year-old AIDS patient with influenza A infection who developed pseudomembranous AT without corticosteroid use or immunosuppressive therapy.